PENGOLAHAN BAT GUANO MENJADI PUPUK HAYATI CAIR SEBAGAI UPAYA MENEKAN PENGGUNAAN PUPUK KIMIA SINTETIK BAGI PETANI JAGUNG DESA LAINUNGAN KABUPATEN SIDRAP, SULAWESI SELATAN - Alimuddin Ali; Muhammad Hasan; Muhammad Junda; Muhiddin Palennari; Herlina Rante (LPPM Uncen, 2022)
The development of modern agriculture dynamic has contributed to encouraging the continuous utilizing of synthetic chemical fertilizers by farmers. On the other hand, the fertilization cost are increasing and scarcity occurs making its difficult for farmers to obtain, so its an impact to fertilization delays as well as production. In addition, the long-term impact of application of synthetic chemical fertilizers causing in a number of problems to crop cultivation. Therefore, the efforts are needed to reduce the utilization of synthetic chemical fertilizers, as well as reduce them by substitution of biological fertilizers. This effort was caused by the knowledge and skills of the farmer in making biofertilizers is lack. On the other hand, there are many materials sources to making biological fertilizers, thus encouraging efforts to training of target partners, especially corn farmers in Lainungan Village, Sidrap distric, South Sulawesi. This activity takes place from July to September 2022. This activity is not only attended by farmers, but also attended by community leaders. The results of this activity indicate that the target partners have the knowledge and skills to process guano bat into an biofertilizer. The results of the analysis of the use of biofertilizers are still in the field trial stage, so it is hoped that this product will be able to give a real impact in suppressing the use of biofertilizers and be able to achieve the target of corn farmers to substitute up to 50% of biofertilizers.Keywords: Guano bat; biofertilizer; corn farmer